2005
DOI: 10.1017/s0031182005007997
|View full text |Cite
|
Sign up to set email alerts
|

Altered drug influx/efflux and enhanced metabolic activity in triclabendazole-resistant liver flukes

Abstract: Triclabendazole (TCBZ) is a halogenated benzimidazole compound that possesses high activity against immature and adult stages of the liver fluke, Fasciola hepatica. The intensive use of TCBZ in endemic areas of fascioliasis has resulted in the development of liver flukes resistant to this compound. TCBZ sulphoxide (TCBZSO) and TCBZ sulphone (TCBZSO2) are the main molecules recovered in the bloodstream of TCBZ-treated animals. In order to gain some insight into the possible mechanisms of resistance to TCBZ, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
140
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(149 citation statements)
references
References 47 publications
9
140
0
Order By: Relevance
“…The Sligo isolate has been shown to be resistant to the action of TCBZ in vivo Coles and Stafford 2001;McCoy et al 2005) and has been used in a number of in vitro studies (Robinson et al 2002(Robinson et al , 2004Alvarez et al 2005). Four-week-old juvenile flukes were removed from the livers of the rats under sterile conditions in a laminar flow cabinet.…”
Section: Methodsmentioning
confidence: 99%
“…The Sligo isolate has been shown to be resistant to the action of TCBZ in vivo Coles and Stafford 2001;McCoy et al 2005) and has been used in a number of in vitro studies (Robinson et al 2002(Robinson et al , 2004Alvarez et al 2005). Four-week-old juvenile flukes were removed from the livers of the rats under sterile conditions in a laminar flow cabinet.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, TCBZ-resistant isolates have been shown to carry out the metabolism of TCBZ at a significantly higher rate than that by TCBZ-susceptible isolates (Robinson et al 2004;Alvarez et al 2005). It is this enhancement of oxidative metabolism that has been suggested as a possible mechanism of resistance within the fluke.…”
Section: Introductionmentioning
confidence: 99%
“…It is this enhancement of oxidative metabolism that has been suggested as a possible mechanism of resistance within the fluke. The FMO system represents the main metabolic pathway for the metabolism of TCBZ to triclabendazole sulphoxide (TCBZ.SO) by F. hepatica (Alvarez et al 2005). A previous scanning electron microscopical study showed that inhibition of this system by methimazole (MTZ) leads to more severe surface changes in a TCBZresistant isolate when incubated with TCBZ and TCBZ.SO than when incubated in the drug alone (Devine et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The FMO system probably represents the main pathway for the metabolism of TCBZ to TCBZ.SO, while the CYP 450 system probably plays a greater role in the conversion of TCBZ.SO to TCBZ. SO 2 (Alvarez et al 2005).…”
Section: Introductionmentioning
confidence: 99%